2017
DOI: 10.1002/elsc.201700001
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced growth and total fatty acid production of microalgae under various lighting conditions induced by flashing light

Abstract: Microalgae are gaining importance as a source of high‐value bioproducts. However, data regarding optimization of algal productivity via variation of environmental factors are lacking. Here, we evaluated a novel lighting method for the enhancement of biomass and total fatty acid (TFA) productivities during algal cultivation. We cultivated six different algal strains (Chlorella vulgaris KCTC AG10002, Acutodesmus obliquus KGE18, Uronema sp. KGE03, Micractinium reisseri KGE19, Fragilaria sp., and Spirogyra sp.) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, Chandra et al [ 64 ] established that the content of both linoleic and α-linolenic acids increases together with an increase in light intensity, which is a continuous lighting condition for an optimal photoperiod. Choi et al [ 65 ] studied the dependence of biomass productivity and total fatty acid content in microalgae on various lighting conditions (continuous light, light-dark cycle, continuous darkness and continuous darkness with additional flashing light). The analysis found that the use of flashing light significantly increased the growth rate of Chlorella vulgaris and the concentration of fatty acids in the biomass.…”
Section: Microalgae Lipidsmentioning
confidence: 99%
“…On the other hand, Chandra et al [ 64 ] established that the content of both linoleic and α-linolenic acids increases together with an increase in light intensity, which is a continuous lighting condition for an optimal photoperiod. Choi et al [ 65 ] studied the dependence of biomass productivity and total fatty acid content in microalgae on various lighting conditions (continuous light, light-dark cycle, continuous darkness and continuous darkness with additional flashing light). The analysis found that the use of flashing light significantly increased the growth rate of Chlorella vulgaris and the concentration of fatty acids in the biomass.…”
Section: Microalgae Lipidsmentioning
confidence: 99%
“…On the other hand, a later study has shown that flashing lights could significantly increase the total fatty acid (TFA) content of C. vulgaris in addition to its growth rate either the lighting period was continuous or cycling (light-dark). 28 On the other hand, Zhao and colleagues showed that red light wavelength at the intensity of 1200-1600 μmol/m 2 /s is optimum for microalgal growth. 29 More studies regarding light impact on microalgae growth and production are summarized in Table 1.…”
Section: Process Technologymentioning
confidence: 99%
“…The plant growth hormone (IAA) was analyzed by the HPLC‐UV/Vis detector (YL9100 HPLC system, YL9120 UV/Vis Detector, Young Lin Instrument, Anyang, Korea). For the analysis of IAA, 15 days of cultivated whole plant (plant body and root) extracts were prepared using methanol . For the PCR‐DGGE analysis of the rhizobacteria of the plants, soil samples near the plant root surface were collected .…”
Section: Methodsmentioning
confidence: 99%